MENILIK REAKSI KREDIT PERBANKAN ATAS DINAMIKA FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL: STUDI KASUS PADA BANK GO PUBLIC INDONESIA PERIODE 2017-2020 DENGAN METODE REGRESI DATA POOL - Gregorius N. Masdjojo; Titiek Suwarti; Listiyorini Wahyu Widati (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
This study aims to analyze the influence of internal and external factors on bank credit. The data was obtained from banks listed on the Indonesian Stock Exchange in the 2017-2020 period. Samples were taken based on the purposive sampling technique. This research uses the data pool regression analysis. Then the selection of the best estimate based on the Chow test to select the Pooled Least Square (PLS) estimate with the Fixed Effect Model (FEM). Then the Hausman test was carried out to select the FEM estimate with the Random Effect Model (REM). The test results found that FEM was the best for further analysis. From the FEM output, it is concluded that Third Party Finance (TPF) and Loan to Deposit Ratio (LDR) have a positive effect on bank credit. Meanwhile, Non Perfoming Loan (NPL) and Capital Adequacy Ratio(CAR) do not affect bank credit. Then Economic Growth affects bank credit negatively. The Market Interest Rate has a positive effect on bank credit. The three state-owned banks have a higher ability to provide credit than the other banks in the sample of this study.